2011
DOI: 10.1111/j.1467-9507.2011.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Anger Expression and Persistence in Young Children

Abstract: This study investigated anger expression during toy removal (TR) in 92 young Chinese children, two to five years of age, and its relations to their persistence in responding to obstacles during two challenging tasks with highly desirable goals [TR and locked box (LB)] and one challenging task with a less desirable goal [impossible perfect circles (IPC)]. Anger expression during TR was positively associated with persistence during TR and LB but not during IPC. The results highlighted the positive effects of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…This is consistent with results that approach‐oriented preschoolers, who are characterized by preference for challenging tasks and demonstrating higher optimism, exhibit higher attention skills in orienting, vigilance, and executive tasks, than avoidance‐oriented children, who are characterized by avoiding challenges and exhibiting negativity (Chang & Burns, 2005). In addition, evidence that anger, an adaptive reaction elicited by arm restraint, is the by‐product of both interest in and focus on desired goals (Lewis & Ramsay, 2005) or rewarding information (Ford et al., 2010), and persistence in mastery situations (He et al., in press; Kearney, 2004), supports the current relations between anger and attention focusing. Moreover, other work has found that positive affect is associated with longer attention focusing in a learning task (Rose, Futterwelt, & Jankowski, 1999).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This is consistent with results that approach‐oriented preschoolers, who are characterized by preference for challenging tasks and demonstrating higher optimism, exhibit higher attention skills in orienting, vigilance, and executive tasks, than avoidance‐oriented children, who are characterized by avoiding challenges and exhibiting negativity (Chang & Burns, 2005). In addition, evidence that anger, an adaptive reaction elicited by arm restraint, is the by‐product of both interest in and focus on desired goals (Lewis & Ramsay, 2005) or rewarding information (Ford et al., 2010), and persistence in mastery situations (He et al., in press; Kearney, 2004), supports the current relations between anger and attention focusing. Moreover, other work has found that positive affect is associated with longer attention focusing in a learning task (Rose, Futterwelt, & Jankowski, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Consistent with a motivational approach/avoidance systems model of temperament, positive reactivity is associated with exuberance, a behavioral style in which children display high joy and approach (Fox et al., 2001; Hane et al., 2008). Anger is also considered part of the approach system, as it is suggested to support approach behavior toward goals (Derryberry & Rothbart, 2001; He, Xu, & Degnan, in press) and is linked to approach‐related patterns of left frontal EEG asymmetry (Carver & Harmon‐Jones, 2009). However, in contrast to the current hypothesis, observed positive reactivity and anger were unrelated in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, emotion expression may be less associated with teacher–student closeness because other factors, such as teacher characteristics unaccounted for in this study, may also be critical for developing a close relationship with teachers (de Jong et al, ; Jerome et al, ). Alternatively, anger and frustration in the classroom context may sometimes reflect approach motivation during academic‐related tasks (He, Xu, & Degnan, ), indicating academic persistence that might be favorable to teacher–student relationship quality.…”
Section: Discussionmentioning
confidence: 99%
“…This task was modified from the Laboratory Temperament Assessment Battery (Goldsmith, Reilly, Lemery, Longley, & Prescott, 1994) and the study of He et al (2012). The task began with a learning/practice period, during which the experimenter taught the child to open the lock with a key.…”
Section: Locked Boxmentioning
confidence: 99%